Penguatan Desa Mandiri Finansial melalui Literasi dan Pengelolaan Keuangan berbasis Komunitas: Studi Transformasi Desa Juruan Daya - Tri Dyah Prastiti; Berlina Hidayati; Sucipto Sucipto; Tiara Sevi N.; Milawati Milawati (IKIP PGRI Bojonegoro, 2026)
ABSTRACT This community service program aims to strengthen the financial literacy and financial management skills of the Family Welfare Empowerment (PKK) members and Micro, Small, and Medium Enterprise (MSME) actors in Juruan Daya Village, Sumenep Regency. The program targeted PKK members, micro and small business actors, and community representatives through a community-based empowerment approach encompassing needs assessments, focus group discussions (FGDs), interactive training, guided practice utilizing a manual bookkeeping tool (BookNote), small-group mentoring, and reflective evaluation. A total of 28 participants were involved in this program. The outcomes demonstrated an increase in participants' understanding of budgeting, expenditure prioritization, saving strategies, prudent debt management, and the utilization of digital payment services such as QRIS (Quick Response Code Indonesian Standard). Furthermore, the program encouraged more disciplined bookkeeping practices and heightened participants' awareness of financial risks, including online loans,